A New Measure of 19th Century US Suicides - Christoph Kronenberg (Social Indicators Research, 2021)
Suicides hurt families and the US economy with an annual cost of 69 billion. However, little is known about what determined suicide rates in the past. This is likely due to the lack of consistent data prior to the 20th century. In this article, I propose using newspaper suicide mentions for the period 1840–1910 as a proxy measure for suicide and perform several validation exercises. I show that the stylized facts like suicides drop during wars holds for suicide mentions. I also validate the newspaper suicide mentions against sparse suicide mortality data and a novel valence measure. This new measure can be used to assess the relationship between suicides and numerous policy changes happening in the 19th century that previously could not be explored. It thus offers a new research avenue for quantitative historical analyses, which can inform current policy via novel historical insights.
Keywords: 300; Suicide; Newspapers; Proxy